Implikasi Hukum Terhadap Praktik Iklan Pembohongan dalam Perlindungan Konsumen (Studi Kasus Putusan Pengadilan) - Miftahul Jannah; Winda Fitri; Windi Afdal (JURNAL HUKUM PELITA, 2025)
This research aims to examine and understand the legal implications of deceptive advertising practices within the framework of consumer protection, using a case study of court rulings. Deceptive advertising refers to false or misleading information in advertisements, intended to gain profit through actions that violate legal and ethical standards. This research employs a qualitative normative method, incorporating a statutory approach and case studies. Data collection relies on secondary sources obtained through literature reviews, including primary, secondary, and tertiary legal materials. The collected data is analyzed using qualitative methods based on the literature review. The findings reveal that regulations concerning consumer protection against deceptive advertising in Indonesia are clearly stipulated in Law Number 8 of 1999 on Consumer Protection (UUPK). The legal implications of deceptive advertising, as evidenced by court rulings, provide a degree of protection for consumers. However, the lack of tangible benefits, such as compensation for consumers based on court decisions, indicates that the position of consumers remains weak in cases involving deceptive advertising.